2021
DOI: 10.3389/fpls.2021.647123
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Role of the Actin Cytoskeleton in Plasmodesmata: A Focus on Formins

Abstract: Cell-to-cell communication in plants is mediated by plasmodesmata (PD) whose permeability is tightly regulated during plant growth and development. The actin cytoskeleton has been implicated in regulating the permeability of PD, but the underlying mechanism remains largely unknown. Recent characterization of PD-localized formin proteins has shed light on the role and mechanism of action of actin in regulating PD-mediated intercellular trafficking. In this mini-review article, we will describe the progress in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Chaperones and RNA helicases may be involved in this process [ 27 , 28 ]. This process may also involve RNA-binding proteins that function as carriers, and their receptors, as well as actin and myosin that can alter plasmodesmal pore size [ 27 , 29 , 30 ]. In our recent study, we found that a catalytic subunit of the RNA exosome, Arabidopsis Ribosomal RNA-Processing Protein 44A (AtRRP44A), controls KN1 and STM mRNA trafficking between cells [ 8 ].…”
mentioning
confidence: 99%
“…Chaperones and RNA helicases may be involved in this process [ 27 , 28 ]. This process may also involve RNA-binding proteins that function as carriers, and their receptors, as well as actin and myosin that can alter plasmodesmal pore size [ 27 , 29 , 30 ]. In our recent study, we found that a catalytic subunit of the RNA exosome, Arabidopsis Ribosomal RNA-Processing Protein 44A (AtRRP44A), controls KN1 and STM mRNA trafficking between cells [ 8 ].…”
mentioning
confidence: 99%
“…As shown in the GO enrichment plot (Figure 6), the transcribed sORFs with enriched GO terms related to actin were detected in both varieties. Actin mainly functions in cellular physiological processes in plants including cell growth, cytokinesis, cell division, and several intracellular trafficking events (Diao and Huang, 2021). This indicates that the transcribed sORFs of C. sativus might play a role in growth and development regulations.…”
Section: Resultsmentioning
confidence: 99%
“…tropomyosin-like proteins) [14]. W PD zidentyfikowano także forminę [15]. Poza tym w PD stwierdzono występowanie ARP2/3 (ang.…”
Section: Błony Pdunclassified